2004
DOI: 10.1136/gut.53.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Systemic antibodies towards mucosal bacteria in ulcerative colitis and Crohn's disease differentially activate the innate immune response

Abstract: Background and aims: The mucosa in ulcerative colitis (UC) is replete with antibody producing plasma B cells and polymorphonuclear leucocytes (PMN). This combination of effector cells requires a crosslinking antigen to evoke an antibody driven PMN inflammatory response via their Fc receptors. The stimulus for activation is thought to be commensal bacteria colonising the gut mucosa. The aim of this investigation was to compare the principal culturable bacterial populations on the rectal mucosa of UC patients, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 57 publications
3
53
1
1
Order By: Relevance
“…In this context, the existence of antibodies directed against certain proteins secreted by the commensal microbiota in the framework of certain autoimmune diseases is known. Some examples of these proteins are porin OmpC from Escherichia coli, porin OmpW from Bacteroides caccae, protein I2 from Pseudomonas fluorescens and flagellin from Clostridium coccoides (Adams et al, 2008;Furrie et al, 2004;Iltanen et al, 2006;Müller et al, 2008). Theoretically, it is possible that certain extracellular proteins secreted by probiotic bacteria might also reach the gut mucosa, acting as molecular effectors responsible for downstream responses in mucosal cells.…”
Section: Proteins Secreted By Probiotic Bacteriamentioning
confidence: 99%
“…In this context, the existence of antibodies directed against certain proteins secreted by the commensal microbiota in the framework of certain autoimmune diseases is known. Some examples of these proteins are porin OmpC from Escherichia coli, porin OmpW from Bacteroides caccae, protein I2 from Pseudomonas fluorescens and flagellin from Clostridium coccoides (Adams et al, 2008;Furrie et al, 2004;Iltanen et al, 2006;Müller et al, 2008). Theoretically, it is possible that certain extracellular proteins secreted by probiotic bacteria might also reach the gut mucosa, acting as molecular effectors responsible for downstream responses in mucosal cells.…”
Section: Proteins Secreted By Probiotic Bacteriamentioning
confidence: 99%
“…Ulcerative colitis, a type of inflammatory bowel disease, is characterized by uncontrolled inflammation in the colon and rectum, recurrent episodes of bloody diarrhea, cramping, abdominal pain, mucosal inflammation and injury (1). Considering the pathogenic mechanisms of ulcerative colitis, it is suggested that deregulation of the pro-/anti-inflammatory systems and antioxidant system may to be involved (2).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD), including Crohn's disease and ulcerative colitis (UC), is a chronic and relapsing inflammatory disease caused by the inflammation and sores in the lining of large intestine and characterized clinically by recurrent episodes of bloody diarrhea, cramping, abdominal pain and histologically by mucosal inflammation and injury [1] . Conventional therapy for UC includes sulfasalazine and other 5-aminosalicylic acid (5-ASA) type of compounds, and in more persistent and/ or severe cases, oral, rectal and parenteral corticosteroids and immunosuppressants are administered [2] .…”
Section: Introductionmentioning
confidence: 99%